2018
DOI: 10.1111/ijd.14357
|View full text |Cite
|
Sign up to set email alerts
|

Superficial CD34 positive fibroblastic tumor: report of three cases and review of the literature

Abstract: Superficial CD34 positive fibroblastic tumor (SCPFT) is a recently recognized, unique neoplasm with distinctive histomorphological features such as high pleomorphism, low mitotic rate, and diffuse CD34 reactivity. Hereby we present three cases of our experience with clinicopathological, morphological, and immunohistochemical characteristics. The patients were a 31-year-old female, 53-year-old female, and 33-year-old male. The tumors were all superficially located; left forearm, medial aspect of the left ankle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Following the initial description in 2014 by Carter et al, 1 several case-series of SCD34FT have been reported, validating the consistent clinicopathological characteristics of these neoplasms. [9][10][11][12] Subsequently, the description of recurrent fusions involving PRDM10 in tumors showing a close resemblance to SCD34FT opened the debate of whether they should be classified as independent entities. In this context, based on the available clinicopathological findings (Table 5), we believe there is compelling evidence for considering these neoplasms as part of the same spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Following the initial description in 2014 by Carter et al, 1 several case-series of SCD34FT have been reported, validating the consistent clinicopathological characteristics of these neoplasms. [9][10][11][12] Subsequently, the description of recurrent fusions involving PRDM10 in tumors showing a close resemblance to SCD34FT opened the debate of whether they should be classified as independent entities. In this context, based on the available clinicopathological findings (Table 5), we believe there is compelling evidence for considering these neoplasms as part of the same spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Both SCD34FT and DFSP can exhibit pleomorphism with CD34-positivity in tumour cells, but DFSP shows a distinctive storiform pattern of spindle cells infiltrating into the subcutaneous tissue. [3,8] Areas with fibrosarcomatous transformation show a typical herringbone pattern with obvious mitotic figures and reduced CD34 expression. There is significantly increased p53 and Ki-67 expression.…”
Section: Discussionmentioning
confidence: 99%
“…They are usually circumscribed lesions with subcutaneous presentation, with little or no deep-muscle involvement, as in our case. [1][2][3][4][5][6][7][8][9] The first case was described by Carter et al 3 in 2014, and, to date, 52 cases have been identified. [1][2][3] The literature presents only case reports, which makes it difficult to establish a treatment guide or clear evidence regarding surgical management and adjuvant modalities, such as chemotherapy or radiotherapy, for this type of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The first case was described by Carter et al 3 in 2014, and, to date, 52 cases have been identified. [1][2][3] The literature presents only case reports, which makes it difficult to establish a treatment guide or clear evidence regarding surgical management and adjuvant modalities, such as chemotherapy or radiotherapy, for this type of tumor. However, the available information reveals good outcomes after surgical resection, with no postoperative local recurrences.…”
Section: Discussionmentioning
confidence: 99%